Dzielimy się Doświadczeniem Pulmonary hypertension reversibility – how to measure and judge? - Świerad, Marcin; Maruszewski, Marcin; Zakliczyński, Michał; Zębik, Tadeusz; Świątkowski, Andrzej; Gąsior, Mariusz; Poloński, Lech; Kalarus, Zbigniew; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
The paper presents a definition of pulmonary hypertension in relation to potential heart transplant candidates. Diagnosis of pulmonary hypertension in a heart transplant candidate obliges the transplant team to measure its reversibility, i.e. pulmonary vasculature reaction to vasodilator injection. The protocols and drugs applied in pulmonary hypertension reversibility measurement allow one not only to control the vasculatory status of pulmonary circulation but also to predict the early survival rate post heart transplantation. The decision to qualify or disqualify the patient for heart or heart-lung transplantation should be made after a thorough analysis of various risk factors, among which pulmonary hypertension should be precisely measured and analyzed.